Beyond segments in movement: a "small" agenda for research in the professions. Issue 8 (19th October 2015) - Ramirez, Carlos; Stringfellow, Lindsay; Maclean, Mairi
Abstract : Purpose: – The small accounting practice, despite being the most numerous part of the profession by number of firms, remains largely under-researched. Part of the reason the small practice category remains elusive is that researchers find it difficult to precisely define the object to study, and yet, this may be precisely the reason for studying it. Envisaging how this category is "represented" in institutionalized settings, constitutes a rich agenda for future research as it allows the small practitioner world to be connected to the issue of intra-professional segmentation. The paper aims to discuss these issues. Design/methodology/approach: – This paper proposes reinvigorating research around Bucher and Strauss' (1961) conceptualization of professions as "segments in movement". At the same time as advocating a better investigation of the small practitioner segment itself, it suggests to take the latter as an example to further explore the vision of professions as segments "more or less delicately held together". To this end, there is a potential for cross-fertilization between Bucher and Strauss' research programme and a range of other theoretical frameworks. Findings: – The discussion points towards how small practice, as a segment whose history and characteristics reflect the different struggles that have led to the creation of the professional accounting body and marked its subsequent evolution, is far from insignificant. Segmenting the profession in categories related to "size" offers an opportunity to deal with an under-investigated aspect of professions' sociology and history, which encapsulates its inherent diversity and hierarchy. Whilst the professional body may replicate the hierarchy that structures broader society, the meaning of small itself, within a hierarchy of organizations, is also a relative concept. It is politically charged, and must be delicately managed in order to maintain harmony within the polarized professional space. Originality/value: – The small practitioner has been much overlooked in the accounting literature, and the literature on the professions has overemphasized aspects of its cohesiveness. The authors contribute a revitalized agenda for researchers to explore the dynamics of heterogeneity and unity in the professional body, by focusing a lens on the small practice and extending the "segments in movements" premise beyond the functional division of professions.